2022
DOI: 10.1016/j.japh.2022.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home drug delivery on drug-related problems: preliminary evidence for improved patient outcomes during the COVID-19 pandemic in Thailand

Abstract: Background Drug-related problems cause severe disabilities, premature deaths, and unnecessary costs. Telepharmacy offer easier access to needed medications, preventing DRPs. Adoption has been slow, and it is unclear what aspects of telepharmacy are most important. The COVID-19 pandemic disrupted health services, forcing the rapid adoption of telepharmacy. In Phayao, Thailand, a program was implemented for home delivery of drugs for chronic disease patients. Objectives T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Therefore, there is a need for studies with a stronger methodological rigor to thoroughly address this regard. Despite the fact that the implementation of home delivery of medications is associated with several pros, such as treatment continuity, economic savings, decongestion of the healthcare centers, avoiding traveling expenses, saving patients' time, and enhancing the quality of life (10,17), there are potential drawbacks that should be highlighted. First, implementing a home drug delivery service without integrating it with the telepharmacy system, compromises the optimal provision of the pharmaceutical care (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a need for studies with a stronger methodological rigor to thoroughly address this regard. Despite the fact that the implementation of home delivery of medications is associated with several pros, such as treatment continuity, economic savings, decongestion of the healthcare centers, avoiding traveling expenses, saving patients' time, and enhancing the quality of life (10,17), there are potential drawbacks that should be highlighted. First, implementing a home drug delivery service without integrating it with the telepharmacy system, compromises the optimal provision of the pharmaceutical care (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, an important fact that this study revealed is that a high proportion of these experienced pharmacists believe that much important information may be skipped if medications are not dispensed face to face at the pharmacy site. This could be particularly true in patients on complex regimens, such as anticoagulants, insulin therapy, and antiepileptic drugs ( 10 ). In light of these findings, integration of telehealth services among home delivery services would be extremely important in covering this missing aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, a recent study conducted in Thailand reported that the prevalence of drug-related problem from home drug delivery was as high as 49% and the most common type of errors was associated with change in drug packaging and drug brand. The latter may lead to confusion and precipitate other types of drug-related problems, such as patient's lack of compliance and adverse events in case the drug-related problem was not detected 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common types of these errors include for instance, medicines delivered to wrong patients, wrong labelling in the delivered package, inappropriate patient counseling, and suboptimal medication therapy management. 25,26 As such, more research is needed to explore this service, and maximize the benefit from it by understanding the public perspective 8 . Thus, the aims of this study are to investigate the public's perception of the home delivery of medication service that was offered by some community pharmacies in Jordan and to evaluate factors affecting the use of this service.…”
Section: Introductionmentioning
confidence: 99%